Places of engagement : reflections on Higher education in 2040 : a global approach - Heijnen, Armand, 1954-; Vaart, Rob van der; Zwaan, Bert van der, 1952- (AUP, 2018)
In his book 'Higher Education in 2040 - A Global Approach' (2017) Bert van der Zwaan developed a thought-provoking vision of the university of the future, based on a thorough discussion of current trends and on a large number of conversations with leaders in higher education worldwide. This book, 'Places of Engagement', offer reflections on themes discussed by Van der Zwaan, written by twenty of his peers and other opinion leaders from around the world. The book was written in honour of Bert van der Zwaan at the occasion of his departure as Vice-Chancellor of Utrecht University. With contributions by John Sexton, José van Dijck, Karl Dittrich, Dilly Fung, Michael Crow and many others.